2006
DOI: 10.1146/annurev.soc.31.041304.122220
|View full text |Cite
|
Sign up to set email alerts
|

Low Fertility at the Turn of the Twenty-First Century

Abstract: In the past few decades, demographic concerns have shifted from rapid population growth fueled by high fertility to concerns of population decline produced by very low, sub-replacement fertility levels. Once considered a problem unique to Europe or developed nations, concerns now center on the global spread of low fertility. Nearly half of the world's population now lives in countries with fertility at or below replacement levels. Further, by the mid-twenty-first century three of four countries now described a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(108 citation statements)
references
References 93 publications
2
99
0
7
Order By: Relevance
“…A more substantive reason behind the female focus of fertility research is the theoretical notion that women are the driving force behind fertility decisions and the postponement of parenthood. This notion is based on the assumption that having a child involves greater investments of time and energy for women than for men, because even though women's educational attainment and labor force participation levels have increased significantly in recent decades, they continue to perform the majority of childcare and household tasks (Kühhirt 2011;Morgan and Taylor 2006). The birth of the first child is, indeed, associated with indirect and direct costs for women's careers in virtually all industrialized countries (Amuedo-Dorantes and Kimmel 2005; Budig and England 2001;Ellwood, Wilde, and Batchelder 2004;Gangl and Ziefle 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A more substantive reason behind the female focus of fertility research is the theoretical notion that women are the driving force behind fertility decisions and the postponement of parenthood. This notion is based on the assumption that having a child involves greater investments of time and energy for women than for men, because even though women's educational attainment and labor force participation levels have increased significantly in recent decades, they continue to perform the majority of childcare and household tasks (Kühhirt 2011;Morgan and Taylor 2006). The birth of the first child is, indeed, associated with indirect and direct costs for women's careers in virtually all industrialized countries (Amuedo-Dorantes and Kimmel 2005; Budig and England 2001;Ellwood, Wilde, and Batchelder 2004;Gangl and Ziefle 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Morgan and Taylor (2006) suggested that it is precisely this question that needs to be addressed in order to understand contemporary low fertility. Several researchers have argued that the postponement or abandoning of fertility intentions may be an underlying driver of low fertility (Hagewen and Morgan 2005;Spéder and Kapitany 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cross-country fertility differences today are to a large extent due to differences in second-birth rates, and to a much lesser extent to an increasing rejection of parenthood. Apparently, the biological, psychological and social incentives remain strong enough for most people to want at least one child (Kohler et al 2006;Morgan and Taylor 2006). The gap between lowest-low and ordinary low fertility crucially depends on parity progression after the first birth: second-birth rates are typically low in the very low fertility countries of southern as well as central and eastern Europe.…”
Section: Introductionmentioning
confidence: 99%